Çukuriçi Höyük 5: Stratigraphie und Architektur der frühen Bronzezeit - Grasböck, Stefan; Bratschi, Tina; Horejs, Barbara; Schwall, Christoph (Oriental and European archaeology, 2023)
The publication contains the research results on the Early Bronze Age stratigraphy and architecture of the excavations at the Çukuriçi Höyük (Turkey). The Eraly Bronze Age features are presented in this volume and evaluated in terms of architectural history. Finally, there is a cultural-historical evaluation of the Early Bronze Age sattlement as well as an embedding in the region ofer Western Anatolia and the Eastern Aegean